The Influence of Javanese-Arabic Translation Methods by Tafsir Al-Jalalain towards the Students’ Mastery in Nahwu - Damayulfi, Andini Cita; Firdaus, Mochammad; Adam Ibrahim, Faisol Mahmud (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
The Arabic-Javanese translation method is one of the Arabic translation methods commonly used in Arabic language teaching and learning in pondok pesantren (Islamic boarding schools) in Indonesia. This method was considered to be able to facilitate students in understanding Nahwu. This article aimed to determine the influence of the use of Javanese-Arabic translation methods in the book of Tafsir Jalalain on the mastery of nahwu of the students and its influence. Quantitative approaches and bivariate correlational analysis were uesed. The data about the students’ mastery in nahwu was collected by using multiple choice test instruments and essays which were tested on 6th grade students of Madrasah Diniyah Islamic Boarding School Karangasem Muhammadiyah Lamongan with a sample of 20 students. The sample determination was based on a simple random sampling technique. There was a significant positive influence between Javanese-Arabic translation and the students’ mastery in nahwu, which was 0.910 on the sig. 0.000 or <0.05. In addition, based on the results of the regression linear test, an increase in the Javanese-Arabic translation score will increase the nahwu mastery score by 1,014. Hence, it could be stated that use of the Javanese-Arabic translation method helped the students in understanding the the rules of nahwu. Based on the findings, the Javanese-Arabic translation method was recommended to be applied in Islamic boarding schools with Kitab Kuning (Yellow Book) learning system, especially for Islamic Boarding Schools in Java.